OBESITY, HYPERLIPIDEMIA, AND HYPERURAECEMIA IN YOUNG AND OLD HYPERTENSIVE PATIENTS - Ahmed, Nazir; Anwar, Waqas; Waqas, Huma (Journal of Ayub Medical College Abbottabad, 2009)
Background: There is strong correlation among hypertension, obesity, hyperlipidemia and hyperuricemia which are important risk factor for the cardiovascular disease. Objective of this study was to assess and compare the prevalence of obesity, hyperlipidemia and hyperuricemia among young and old hypertensive patients in the local setting. Methods: This cross-sectional study was conducted at medical Out-patient Department at Shahina Jamil Teaching Hospital, Abbottabad, from September 2007 to February 2008. Eighty-six patients seen in the medical outpatient department were enrolled in the study. Patients with age 15 years or above and diagnosed as case of systemic hypertension were included. Patients with endocrine disease, pregnancy, coarctation of aorta, and renal disease leading to hypertension were excluded from the study. Results: Total eighty-six patients with mean age of 53.7±12.9 years were included in the study. Patients were divided into younger age group (age <46 years) and older age group (age ‰¥46 years). Mean Body Mass Index (BMI) was 29.7±5.2 in the younger age group and 26.9±4.7 in the older age group, mean serum cholesterol level was 192.2±14.2 mg/dL in younger age group and 190.9±18.3 mg/dL in the older age group, mean serum triglyceride level was 170.5±13.7 mg/dL in younger age group and 166.6±21.4 mg/dL in the older age group and mean serum uric acid levels were 5.6±0.7 mg/dL in younger age group and 5.7±1.2 mg/dL in the older age group. Overweight and obese patients were 70.9% with its higher prevalence in younger (86.2%) as compared to older patients (63.2%). Hypercholesterolemia was found in 27.9% of the patients, with a frequency of 24.1% in younger patients and 29.8% in the older patients. Hypertriglyceridemia was seen in 66.3% of the patients, with a frequency of 69.0% in younger patients and 64.9% in the older patients. Hyperuricemia was present in 37.2% of the hypertensive patients with a frequency of 34.5% in the younger patients and 38.6% in the older patients. Conclusion: Hypercholesterolemia, hypertriglyceridemia, and hyperuricemia are not associated with the age of the hypertensive patients. Increased BMI is more frequent in the young as compared to the old hypertensive patients. Keywords: hypertension, obesity, hypercholesterolemia, hypertriglyceridemia, hyperuricemia